Validation of a genome-wide polygenic score for body mass index in South Asians - Menon, Ramesh; Khan, Nikhat; Charugulla, Sandeep; Bassi, Akshi; Dangare, Pooja; Dedaniya, Akshay; Pant, Aakanksha; Anjanappa, Rammurthy; Samson, Praveena L.; Satagopan, Uthra; Murugan, Sakthivel; Naikawadi, Amol; et al. (Frontiers in Genetics, 2025)
Obesity is a complex disorder, manifested by the interaction of inherited and environmental factors and modulated by a person’s lifestyle habits. India has witnessed more than a two-fold increase in the number of overweight adults in the last 30 years. The polygenic risk score (PRS) quantitatively measures an individual’s risk for common diseases. The PRS for obesity have been validated in the Caucasian population but not in the South Asian (SAS) population. In this study, we benchmarked and validated the existing genome-wide PRS model of obesity with 2.1 million variants in the SAS population. We analyzed a total of 14,263 individuals from three different South Asian cohorts. We compared the risk score with the body mass index (BMI) categories (underweight, normal weight, overweight, and obese) in all three cohorts. High PRS was associated with increased BMI in all the three cohorts. This study also compared validation results from another population-specific PRS model for the BMI. We conclude that high PRS is associated with high BMI in South Asians. Our study suggests that the PRS score can perhaps be an early predictor of overweight and obesity in the South Asian population.